2020
DOI: 10.1002/kin.21365
|View full text |Cite
|
Sign up to set email alerts
|

Esterification reaction kinetics of acetic acid and n‐pentanol catalyzed by sulfated zirconia

Abstract: This study reports experimental data and kinetic modeling of acetic acid esterification with n‐pentanol using sulfated zirconia as a catalyst. Reactions were carried out in an isothermal well‐mixed batch reactor at different temperatures (50‐80°C), n‐pentanol to acid molar ratios (1:1‐3:1), and catalyst loadings (5‐10 wt% in relation to the total amount of acetic acid). The reaction mechanism regarding the heterogeneous catalysis was evaluated considering pseudo‐homogeneous, Eley–Rideal, and Langmuir–Hinshelwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Sulfated zirconia (SZ) is well established as a robust and efficient solid acid catalyst for a variety of reactions of high industrial importance, such as hydrocarbon isomerization, methanol conversion to hydrocarbons, alkylation, acylation, esterification, dehydration, and Fischer–Tropsch processes. More recently, sulfated zirconia has also emerged as a promising catalyst for several biorefinery processes, such as esterification, biodiesel preparation, furfural synthesis and conversion, condensation of ketones, glycerol utilization, and, conversion of CO 2 to light olefins . Among the biorefinery processes, the upgrading of biomass derived volatile fatty acids (C 3 –C 6 ) to corresponding ketones (ketonization reactions) is a promising strategy for the synthesis of biofuels.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfated zirconia (SZ) is well established as a robust and efficient solid acid catalyst for a variety of reactions of high industrial importance, such as hydrocarbon isomerization, methanol conversion to hydrocarbons, alkylation, acylation, esterification, dehydration, and Fischer–Tropsch processes. More recently, sulfated zirconia has also emerged as a promising catalyst for several biorefinery processes, such as esterification, biodiesel preparation, furfural synthesis and conversion, condensation of ketones, glycerol utilization, and, conversion of CO 2 to light olefins . Among the biorefinery processes, the upgrading of biomass derived volatile fatty acids (C 3 –C 6 ) to corresponding ketones (ketonization reactions) is a promising strategy for the synthesis of biofuels.…”
Section: Introductionmentioning
confidence: 99%
“…Both the non-isothermal approach, as well as the v-T flash calculations, are further described. In this work, the reaction rate is represented using an activity-based Langmuir−Hinshelwood rate law, considering that the surface reaction is the rate-controlling step, 19 according to eqs 3−5, 15 ) eq eq R 1 1…”
Section: Methodsmentioning
confidence: 99%
“…In this work, the reaction rate is represented using an activity-based Langmuir–Hinshelwood rate law, considering that the surface reaction is the rate-controlling step, according to eqs –, where k° and K eq ° are the kinetic and equilibrium constants at a reference temperature, E a is the activation energy, R is the universal gas constant, T is the temperature, Δ H R is the reaction enthalpy, which is assumed as constant in this formulation, K ads, i is the adsorption constant of each i component, and a i is the activity of each i product or reactant. In an isofugacity approach ( ϕ–ϕ ), the activity of a given component in a mixture in a specific phase is defined as (eq ): where x i and γ i are the mole fraction and activity coefficient of a certain component, respectively, and ϕ̂ i and ϕ i are the fugacity coefficients of a component in a mixture and as a pure component at the same temperature and pressure.…”
Section: Methodsmentioning
confidence: 99%
“…An important structural attribute of a catalyst is related to the rate of the esterification reaction. Several esterification kinetic studies have been reported using various feedstocks and catalysts (Gao et al, 2020;Hamerski et al, 2020;Kusumaningtyas et al, 2017;. The previous study employed the zeolite-sulfonated biochar derived from biomass-based such as molasse for the catalytic esterification of FFA derived from sludge palm oil.…”
Section: Introductionmentioning
confidence: 99%